Forradalom – Tapasztalat – Várakozás: (Kemény Zsigmond: Forradalom után) - Török, Lajos (Studia Litteraria, 2014)
Zsigmond Kemény wrote his pamphlet Forradalom után („After the Revolution”) a year after the Hungarian Revolution of 1848-1849. In his work he analyses the years of the Revolution and the political events of the 25 years preceding it. According to his perspective, the Revolution had led to a national catastrophe that may render the future of the Hungarian nation as uncertain. The aim of this essay is to investigate the means by which Kemény seeks to re-interpret the political events and leaders of the time between 1825 and 1849 in order to restore the Hungarians’ historical continuity, broken by the Revolution. In the analysis I shall examine the semantic layers of the notion ‘revolution’ used in the pamphlet, Kemény’s collective views of the future and his opinion of Lajos Kossuth.